2020
DOI: 10.1111/ele.13664
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering patterns of freshwater positive interactions using meta‐analysis: Identifying the roles of common participants, invasive species and environmental context

Abstract: Positive interactions are sensitive to human activities, necessitating synthetic approaches to elucidate broad patterns and predict future changes if these interactions are altered or lost. General understanding of freshwater positive interactions has been far outpaced by knowledge of these important relationships in terrestrial and marine ecosystems. We conducted a global meta‐analysis to evaluate the magnitude of positive interactions across freshwater habitats. In 340 studies, we found substantial positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 147 publications
5
30
0
3
Order By: Relevance
“…Context dependence is commonly and increasingly invoked in ecology (Appendix S1, Figure S1, and Table S1 in the supplemental information online) [11][12][13][14][15][16][17], as well as in other fields typified by high complexity, large scales, and heavy reliance on observational studies, such as conservation biology [18,19], evolutionary biology [20,21], and epidemiology [22,23]. Context dependence provides a convenient shorthand to describe variation within and between (potentially myriad) studies and is reported across all study types [24][25][26][27][28]. However, because context dependence can result from many processes (as discussed below), unless the underlying causes are identified, concluding that outcomes are context dependent provides little insight by itself.…”
Section: The Prevalence and Problem Of Context Dependencementioning
confidence: 99%
“…Context dependence is commonly and increasingly invoked in ecology (Appendix S1, Figure S1, and Table S1 in the supplemental information online) [11][12][13][14][15][16][17], as well as in other fields typified by high complexity, large scales, and heavy reliance on observational studies, such as conservation biology [18,19], evolutionary biology [20,21], and epidemiology [22,23]. Context dependence provides a convenient shorthand to describe variation within and between (potentially myriad) studies and is reported across all study types [24][25][26][27][28]. However, because context dependence can result from many processes (as discussed below), unless the underlying causes are identified, concluding that outcomes are context dependent provides little insight by itself.…”
Section: The Prevalence and Problem Of Context Dependencementioning
confidence: 99%
“…Positive biotic interactions are recognized as important drivers of species distributions (Holt et al 2002, Afkhami et al 2014, Albertson et al 2021). However, much less is known about the role of positive interactions in driving large-scale distribution patterns (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, much less is known about the role of positive interactions in driving large-scale distribution patterns (e.g. metapopulation) because emerging patterns and consequences of positive interactions have been almost exclusively studied at local scales (Peoples and Frimpong 2016, Arnhold et al 2019, Albertson et al 2021). Here, using a regional fish dataset in the Midwestern US, we unveiled the critical roles of positive interactions in determining the metapopulation-level relationship between hosts and beneficiary stream fishes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations